THE IMPORTANCE OF FORMING GRAMMATICAL RULES IN THE PROCESS OF TEACHING ENGLISH IN PRIMARY GRADES (Web of Teachers: Inderscience Research, 2024)
This article describes the specific features of the development of listening comprehension skills of high-grade English language learners. Also, in educational institutions, teachers began to pay great attention to teaching their students not only to speak fluently, but also to listen and understand. In order to master and use a new language perfectly, it is necessary to form existing knowledge and learn all the necessary information based on language receptive skills.